Dielectric-metallic double-gradient composition design for stable Zn metal anodes - Yang, Jin-Lin (2023)
The commercial implementation of aqueous Zn-ion batteries is being impeded by the rampant dendrite growth and exacerbated side reactions on the Zn metal anodes. Herein, a 60 nm artificial protective layer with spatial dielectric-metallic gradient composition (denoted as GZH) is developed via Zn and HfO2 cosputtering. In this design, the top HfO2 layer with high permittivity and low electronic conductivity effectively suppresses hydrogen evolution. The intermediate Zn-rich oxide region promotes the dendrite-free Zn deposition and reinforces the contact between Zn and the sputtered layer. This design allows stable battery operation at high currents. Symmetric cells with Zn-GZH exhibit stable voltage separation over 500 h at 10 mA cm-2 with a cutoff capacity of 5 mAh cm-2. When paired with a vanadate cathode, the full-cell battery delivers a capacity retention of around 75% after 2000 cycles. This design concept may apply to other aqueous metal batteries.